4th Industrial Revolution: View from the LIS Professionals in Bangladesh - Nasiruddin, Md (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
The study has aimed to conduct a countrywide library survey for measuring LIS Professionals’ knowledge, attitude and practices concerning 4th Industrial Revolution in the current context of Bangladesh. Both desk and field research methods have been applied with a view to explore the perception of the Bangladeshi library professionals about the 4th IR. Library Professionals have been treated as a vital knowledge-force as they are playing a very dynamic role in the universal diffusion and advancement of knowledge and education around the globe for creating knowledge based society. The survey has been designed with a total population of 340 LIS Professionals from 50 libraries belonging to three categories of which 20 are government public libraries, 10 special libraries and 20 academic libraries (especially the Honours College Libraries affiliated under National University of Bangladesh). Data has been collected from the respondents through questionnaire method and have been analyzed using simple SPSS. Findings revealed that the level of knowledge of the LIS Professionals regarding ICT skills associated with 4thIR to some extent is poor. Findings also revealed that their attitude towards embracing the 4thIR to some extent is still negative. LIS professionals whose mindset is to provide traditional library services instead of innovative services are becoming apprehensive to adopt the changing technologies. They do not like to practice innovative library to not intend to learn and handle advanced technologies to face the challenges of the 4th IR. The study has attempted to find out the reasons behind this. It has also suggested ‘the things to be done’ by the LIS Professionals to cope up with the sophisticated technologies associated with the 4th IR. NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. 39-56